The role of the media in improving the sense of tolerance in the minds of young people in ensuring their spiritual security (Eurasian Research Bulletin, 2022)
In today's modern conditions, the presence of problems at the spiritual and moral level of many young people is becoming completely clear to the public. The low spiritual level of many young people, the shallow state of their social consciousness, the weak will, the obsession with foreign mass culture are being formed as a threat to the spiritual life of society. It is situations in which they manifest manifestations of egocentrism, mannerism and individualism, retreat from our national traditions, alienation from values, lack of respect for traditions, blind implementation of imitation of Western culture